2022
DOI: 10.29040/ijebar.v6i2.5208
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Perceived of Service Quality, Perceived of Website Quality, and Perceived of Website Reputation on Purchase Intention: The Mediation Role of Trust in Online Shopping

Abstract: This study aims to determine the effect of perceived of service quality, perceived of website quality, and perceived of website reputation on purchase intention through the mediating role of trust in online shopping. This research uses a quantitative method with Smart PLS software. A variable measurement scale is carried out using a likert scale. The sample in this study were university students and the general public with an age range of 17-56 years who had used the website of the e-commerce application. Diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…H1 shows that the perceived reputation variable has a positive and significant effect on e-purchase intention. The results of this research are in line with research conducted by (Mohseni et al, 2018) and (Utama et al, 2022) which emphasize that consumers tend to do online shopping activities if a company has a good reputation. Perceived reputation in customers can continue to grow if companies continue to improve their own reputation, this will also increase e-purchase intention in customers.…”
Section: F Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…H1 shows that the perceived reputation variable has a positive and significant effect on e-purchase intention. The results of this research are in line with research conducted by (Mohseni et al, 2018) and (Utama et al, 2022) which emphasize that consumers tend to do online shopping activities if a company has a good reputation. Perceived reputation in customers can continue to grow if companies continue to improve their own reputation, this will also increase e-purchase intention in customers.…”
Section: F Discussionsupporting
confidence: 87%
“…This finding is supported by (Fedorko et al, 2017) who think that the perceived reputation of consumers is an important factor in consumer trust. (Utama et al, 2022) in their research revealed that perceived reputation has a positive effect on consumer trust. The indicators that can be used to measure perceived reputation according to (Doney & Cannon, 1997) and (Koufaris & Hampton-sosa, 2004).…”
Section: The Mediation Role Of E-trust Toward Perceived Reputation Pe...mentioning
confidence: 96%
“…Furthermore, brand image has been shown to have a significant impact on purchase intention, with a positive relationship between brand image and online purchase intention [18]. In addition to these factors, perceived service quality has been found to significantly impact trust and purchase intention, with trust playing a mediating role in the relationship between perceived service quality and purchase intention [19]. Moreover, the influence of brand personality on purchase intention has been explored, revealing a significant effect of brand personality on purchase intention [20].…”
Section: Purchase Intentionmentioning
confidence: 99%
“…According to [28] Buyer trust in online sellers involves the seller's ability to assure buyers that their payment process will be processed safely and efficiently. According to [29], when consumers make purchases online, they will search for information about various products and then choose the product they want to buy.…”
Section: Trustmentioning
confidence: 99%
“…Trust. [28] state that buyer trust in online sellers is based on the seller's ability to persuade customers to ensure transaction security and that payments will be completed immediately. [29], stated that before making an online purchase, customers research several products to determine what they should buy.…”
Section: The Effect Of Perceived Security and Information Quality On ...mentioning
confidence: 99%